The effect of mouth opening levels on acoustic parameters of voice signal - Ghasisin, leila; Abnavi, Fatemeh; Rasimahmoudi, Mahtab; Saberi, Shirin (Canadian Acoustics, 2023)
Objectives: This study examined the effect of three different mouth opening levels on fundamental frequency, jitter, shimmer, harmonic to noise ratio, first formant frequency, second formant frequency and first two formants ratio in Producing vowel /a/. Study design: simple random sampling strategy was used to recruit 36 participants. 18 females and 18 males between age 18 to 29 years were recruited. Methods: the participants sustained vowel /a/ 7 seconds. The first 1 second and the last 1 second of the vowel were omitted in order to eliminate the vowel initiation and termination effect from the audio signal and, thereby, the middle 5 seconds were analyzed to derive acoustic parameters. Seven infrared cameras recorded mouth opening and head movements. Results: The results showed that mouth opening level is only effective on fundamental frequency (p=0.009<0.05), shimmer (p=0.033<0.05) and first formant frequency (p=0.004<0.05). Conclusions: An open jaw posture places the larynx in a lower position which causes a more relaxed phonation that reduce fundamental frequencyand increase shimmer. Mouth opening level has an inverse relationship with first formant frequency.